2006
DOI: 10.1177/0363546505280426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender and Maturity on Quadriceps-to-Hamstring Strength Ratio and Anterior Cruciate Ligament Laxity

Abstract: Female athletes after menarche increase their quadriceps strength greater than their hamstring strength, putting them at risk for anterior cruciate ligament injury. Anterior cruciate ligament-prevention programs based on improving dynamic control of the knee by emphasizing hamstring strengthening should be instituted for girls after menarche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 59 publications
9
112
2
5
Order By: Relevance
“…Based on multiple reports of greater knee laxity values in adult females compared to males, 9,62,72 these data suggest that male values may continue to decrease with advancing age, or that female values may later rise. Our trends from early to late stages of maturation are consistent with the data from Ahmad et al, 2 who found decreased knee laxity in mature (14-18 years) compared to immature (10-13 years) boys, but no change between mature (2 years postmenarche) and immature (premenarche) girls. They attributed these differences to greater strength development in males, greater quadriceps-to-hamstring strength ratios in mature girls, and chronic exposure to estradiol postmenarche in females.…”
Section: 59supporting
confidence: 92%
“…Based on multiple reports of greater knee laxity values in adult females compared to males, 9,62,72 these data suggest that male values may continue to decrease with advancing age, or that female values may later rise. Our trends from early to late stages of maturation are consistent with the data from Ahmad et al, 2 who found decreased knee laxity in mature (14-18 years) compared to immature (10-13 years) boys, but no change between mature (2 years postmenarche) and immature (premenarche) girls. They attributed these differences to greater strength development in males, greater quadriceps-to-hamstring strength ratios in mature girls, and chronic exposure to estradiol postmenarche in females.…”
Section: 59supporting
confidence: 92%
“…2 The unbalanced condition of strength and the hypotrophy of the flexor and extensor muscles of the knee joint are muscle malfunctioncausing factors that alter joint stability, predisposing athletes to injury. [3][4][5] The muscular torque of the quadriceps and hamstrings, as well as their torque ratio (H/Q), is usually evaluated by the isokinetic test. 6 The H/Q ratio is used both clinically and in the laboratory as an indicator of the strength balance between the knee joint muscles.…”
Section: Introductionmentioning
confidence: 99%
“…For muscular capacity, 11 studies have looked into its association with sustaining a non-contact ACL injury (Ahmad, et al, 2006;Bee-Oh, et al, 2009;Bowerman, Smith, Carlson, & King, 2006;Grygorowicz, Kubacki, Pilis, Gieremek, & Rzepka, 2010;Hiemstra, Webber, MacDonald, & Kriellaars, 2007;Holcomb, Rubley, Lee, & Guadagnoli, 2007;Hosokawa, et al, 2011;Mattacola, et al, 2002;Roberts, Ageberg, Andersson, & Fridén, 2007;Wilkerson, et al, 2004;. These studies have associated muscular capacity with risks of acquiring ACL injury, validating ACL screening tools to be used in intervention programs to prevent ACL injury.…”
Section: Reflection On Associative Studiesmentioning
confidence: 99%
“…(Hiemstra, et al, 2007;Mattacola, et al, 2002;Roberts, et al, 2007;Wilkerson, et al, 2004; Isokinetic and isometric peak torques (Ahmad, et al, 2006;Bee-Oh, et al, 2009;Bowerman, et al, 2006;Grygorowicz, et al, 2010;Holcomb, et al, 2007;Hosokawa, et al, 2011). H:Q ratio Muscular Activation (Begalle, et al, 2012;Elias, et al, 2015;Nagano, et al, 2011;R.…”
Section: Author/yearmentioning
confidence: 99%